Does Audit Committee Expertise Mitigate the Impact of Executive Demographics on Risk Disclosure? Evidence from Islamic Banking in Indonesia - Sulhani, Sulhani; Khomsatun, Siti (Journal of Islamic Contemporary Accounting and Business, 2026)
The research aims to obtain evidence and analyze the influence of top management demographics on the disclosure of Islamic banking risk and the moderating role of the audit committee's expertise. Using purposive sampling, this study obtained a sample of 77 observations for the period 2014 – 2019. The first results of the study show that the demographics of top management do no effect on the disclosure of Islamic banking risk, except for the age demographics and experience in Islamic banking of top management. The second results are that the expertise of the audit committee plays a role in strengthening the influence of top management demographics such as age, education background, Islamic banking experience on risk disclosure of Islamic banking. The implications of this study emphasize the importance of the audit committee's expertise, especially those gained from its experience as an internal auditor and/or external auditor, which can support in complementing top management's performance in risk disclosure. It is considered by the board of commissioners in selecting of the audit committee team in order to achieve transparency in risk information.